Europe through the crisis: Discretionary policy changes and automatic stabilisers - Alari Paulus; Iva Valentinova Tasseva (University of Essex, Institute for Social and Economic Research (ISER), 2018)
Tax-benefit policies affect household incomes through two main channels: discretionary policy changes and automatic stabilisers. Although a large body of literature has studied the impact of tax-benefit policy changes on incomes, little is known about the link between automatic stabilisers and the income distribution. We contribute to the literature by studying in detail the contribution of automatic stabilisers and discretionary policy changes to income changes in the EU countries between 2007 and 2014. Our results show that, discretionary policy changes and the automatic stabilisation response of policies more often worked to reduce inequality of net incomes, and so helped offset the inequality-increasing impact of a growing disparity in gross (pre-tax) market incomes. Inequality reduction was achieved mainly through policy changes to benefits and benefits acting as automatic stabilisers. On the other hand, policy changes to and the automatic stabilisation response of taxes and social insurance contributions raised inequality in some countries and lowered it in others.
Keywords: D31; H23; E63; 330; automatic stabilisers; discretionary policy changes; income distribution; decomposition